2007
DOI: 10.3351/ppp.0001.0003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Civilising offensives and ambivalence: the case of British Gypsies

Abstract: Abstract AbstractThis paper utilises Norbert Elias's theory of the civilizing process to examine British society's response to Gypsies and explore the perception of this group as in 'need of corrective treatment'. It demonstrates how state policies towards Gypsies are presented as improving their welfare but are in fact characterised by ambivalence. It is argued that mechanisms employed with the expressed goal of 'civilising' behaviour actually exhibit decivilising elements in terms of their effect upon Gypsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Spatial control through settlement onto permanent camps and spatial cleansing via expulsion from unauthorized camping grounds has created a legacy of displacement and cultural loss; dependence on welfare benefits; poor health outcomes and (for many) a nostalgic yearning for a former way of life (Smith and Greenfields 2013) The geo-physical location of many sites has reinforced both the ability to control the population through segregation and isolation and conveyed the message that those located in such areas were fit for nothing else, reinforcing racialized stereotypes associating Gypsies with dirt, crime and disorder (Belton 2005). The impacts of such racialized spaces are found in 'immediate and oppressive policing' (McVeigh 1997, 22) based on stereotypes of Gypsies and Travellers as a primitive and barbaric minority in need of 'civilizing' (Powell 2007). The relatively under-monitored and inconsistent policing practices regarding the surveillance and control of sites and site residents, suggests that public camps are indeed 'administrative states of exception' where the rule of law, if not outright suspended, is treated in an arbitrary manner and lacks the protections usually afforded to citizens.…”
Section: Urban 'Gypsy Camps': the British Contextmentioning
confidence: 99%
“…Spatial control through settlement onto permanent camps and spatial cleansing via expulsion from unauthorized camping grounds has created a legacy of displacement and cultural loss; dependence on welfare benefits; poor health outcomes and (for many) a nostalgic yearning for a former way of life (Smith and Greenfields 2013) The geo-physical location of many sites has reinforced both the ability to control the population through segregation and isolation and conveyed the message that those located in such areas were fit for nothing else, reinforcing racialized stereotypes associating Gypsies with dirt, crime and disorder (Belton 2005). The impacts of such racialized spaces are found in 'immediate and oppressive policing' (McVeigh 1997, 22) based on stereotypes of Gypsies and Travellers as a primitive and barbaric minority in need of 'civilizing' (Powell 2007). The relatively under-monitored and inconsistent policing practices regarding the surveillance and control of sites and site residents, suggests that public camps are indeed 'administrative states of exception' where the rule of law, if not outright suspended, is treated in an arbitrary manner and lacks the protections usually afforded to citizens.…”
Section: Urban 'Gypsy Camps': the British Contextmentioning
confidence: 99%
“…Thus, the non-rational categorisation of Gypsies and Travellers as presenting a risk to mainstream society has prepared the ground for the imputation of stereotypes which are often exaggerated by the media through the amplification of the risk associated with them (Powell 2008). The recurring stereotypical description of Gypsies and Travellers have been based on negative and imagined images and include notions of a lack of morals, self-restraint, dirt, violence, deviance, laziness and illiteracy which are constructed in opposition to the values of 'respectable' society (Powell, 2007, Morris, 2000. These attributes have been used to justify discriminatory responses to the perceived risks posed by Gypsies and Travellers to the settled community.…”
Section: Gypsies and Travellers -Categorised As 'At Risk'mentioning
confidence: 99%
“…The Anti-social Behaviour Act 2003 empowers schools to apply for a parenting order where a child has been excluded for serious misbehaviour and provides for a fixed penalty system of 'on the spot fines' for parents in cases of truancy. There is evidence that such programmes can lead to positive changes in parenting styles (Scott et al, 2006) however the court ordered elements have been found to be coercive, stigmatising, patronising, controlling, unpopular and ultimately counter-productive (Ghate & Ramella, 2002;Field, 2007, Powell, 2007.…”
Section: Coercive Intervention: Enforcing Parental Responsibilitymentioning
confidence: 99%